Advancing digital frontiers in African economies: lessons learned from firm-level innovations - (:unkn) unknown (My University, 2020)
Multiple initiatives across sub-Saharan Africa are currently leveraging digital technologies to provide transformative solutions to micro, small and medium enterprises (MSMEs) as well as consumers across the region. This paper presents a deeper dive on several promising key players currently pushing frontiers in the digitalisation landscape in sub-Saharan Africa, with a particular focus on West Africa where possible. All highlighted firms use cutting-edge technologies and digital innovations to improve MSME development and job creation by addressing key obstacles to development prevalent in many regions of sub-Saharan Africa, including market failures, missing infrastructures, and insufficient levels of public intervention. Some of the firms described are MSMEs themselves or are in the start-up phase, while others are larger, more established firms that serve MSMEs among their clientele bases. Although the description of sectors, technologies, and enterprises presented in this paper is by no means exhaustive, it nevertheless provides an in-depth picture of several African firms leveraging a diverse set of technologies, serving diverse communities, and offering a wide array of products and services destined for MSMEs and consumers alike.
Keywords: African Research